2011
DOI: 10.5807/kjohn.2011.20.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labor, Social Support, and Depressive Symptoms of Clinical Nurses in a Province, Korea

Abstract: Purpose: This study was conducted to identify the level of emotional labor, social support, and depressive symptoms of nurses, and the relationships among them. Methods: The data were collected from 314 nurses. Surface and deep-acting scales of the Emotional Labor Scale (ELS), the personal resource questionnaire, the organizational support scale, and the Korean version of the Center for Epidemiologic Studies Rating Scale for Depression (CES-D) were used. Collected data were analyzed by descriptive statistics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
1
5
1
2
Order By: Relevance
“…), the prevalence of depressive symptoms among South Korean nurses (38.0% with mild, 16.1% with moderate, 7.6% with moderately severe and 3.1% with severe) is much higher than that of 3.0% in 2011 in the general population (Korea Ministry of Health & Welfare ). A recent cross‐sectional study of 441 nurses reported that approximately 167 (38%) South Korean nurses exhibited depressive symptoms (Kim & Kim ). The prevalence of depressive symptoms in this study showed that 285 (64.8%) nurses suffered from some degree of self‐reported depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), the prevalence of depressive symptoms among South Korean nurses (38.0% with mild, 16.1% with moderate, 7.6% with moderately severe and 3.1% with severe) is much higher than that of 3.0% in 2011 in the general population (Korea Ministry of Health & Welfare ). A recent cross‐sectional study of 441 nurses reported that approximately 167 (38%) South Korean nurses exhibited depressive symptoms (Kim & Kim ). The prevalence of depressive symptoms in this study showed that 285 (64.8%) nurses suffered from some degree of self‐reported depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential benefit of flexible work schedules and higher pay does not protect nurses from occupational harm. In particular, depression among South Korean nurses is increasing (Yoon & Cho 2007, Kim & Kim 2011, Yoon & Kim 2013.…”
Section: Introductionmentioning
confidence: 99%
“…First, the research subjects’ prevalence rate of depression was 16.4 %. This was lower than the rates of hotels and restaurants workers (28.8 %) [ 40 ], bankers (20.6 %) [ 41 ], and clinical nurses (36.3 %) [ 42 ] based on previous studies conducted in Korea using 21 points as the CES-D cut off point. The subjects of this research showed lower prevalence rates of depression because the subjects worked at the first class hotels and 90.1 % of these subjects were permanent employees.…”
Section: Discussionmentioning
confidence: 67%
“…부응하기 위하여 '문재인 케어'로 대변되는 보장성 확대 정 책을 실시하여 진료내역에 대한 각종 평가 제도를 도입하고 이를 비용 지불과 연계시켜 나가고 있다. 이러한 의료 환경 의 급속한 변화로 인하여 병원 등 의료계는 기존의 경영전략 으로는 생존할 수 없다는 인식이 확산되고 있을 뿐 아니라, 환자의 경우에도 심신 상태의 불안정으로 인하여 마음의 여 유가 없을 가능성이 높아 올바른 응대를 받고 있더라도 쉽게 불평을 드러내고 있으므로 환자에 대한 서비스와 환자 만족 은 이제 병원의 경쟁 우위를 좌우하는 주요 요인으로 부각되 고 있다 (Kim HJ et al, 2011). 이에 각 병원들은 품질 높은 의료서비스를 제공하기 위해 노력하고 있으며, 이를 위해서 는 기술적인 부분도 중요하지만 환자와의 접점을 이루는 인 적자원 분야의 중요성이 부각되고 있고, 그 중 병원 인력의 40% 이상을 차지하고 있는 간호사의 역할에 대한 중요성은 더욱 커지고 있다.…”
unclassified
“…이러한 감정노동은 직무스트레스를 높이거나 직무 만족을 저하시키는 요인으로 작용할 수 있다 (Ahn JY et al, 2007). 또한 이직률을 증가시키고 더 나아가 질 높은 간호에 영향을 주는 등 (Zamanzadeh et al, 2013) 조직과 대상자 모두에게 부정적인 영향을 미치게 되므로 (Kim HJ et al, 2011) 감정노동을 최소화 할 수 있는 조직적인 관리 방안이 마련되어야 한다. 한편, 간호사들의 직무스트레스는 업무를 수행하는 과정 에서 필연적이며 적정 수준의 스트레스는 오히려 생존에 필 요한 역동적인 힘으로 작용하기도 하지만 직무스트레스가 과다할 경우 자신의 직업에 대한 회의감이 형성되어 직무를 효과적으로 수행하기 어려울 뿐 아니라, 결과적으로 환자에 대한 간호서비스의 질이 저하되는 것으로 나타나고 있다 (Yoon SH, 2004).…”
unclassified